National Policies for Internationalization—Do They Work? - Matross Helms, Robin; Rumbley, Laura E (International Higher Education, 2016)
As internationalization becomes an increasing priority for higher education worldwide, national governments are implementing policies and programs to promote related activities in their countries. This article categorizes such policies by primary activity type, reviews existing efforts to gauge the effectiveness of such policies, and discusses key factors that can impact policy success.